Comparison of single-pier settlement model and multi-pier settlement model in solving train-track-bridge interaction. Issue 10 (3rd October 2021) - Chen, Zhaowei; Bi, Lin; Zhao, Jiangwei
ABSTRACT: Pier settlement is unavoidable in bridge construction and operation processes, thus the influence of pier settlement on the train-track-bridge coupled system becomes a classic and meaningful topic in railway engineering. Aiming at this practical problem, three interesting works are conducted in this paper: (a) a detailed single-pier settlement model (SPSM) is developed with analytic method; (b) a multi-pier settlement model (MPSM) is also analytically established in detail; and (c) the influences of SPSM and MPSM on the train-track-bridge system are investigated and compared. On this basis, the application ranges for different pier settlement models are suggested from static and dynamic perspectives. Results show that, from static perspective, SPSM and MPSM have the similarity, and results obtained from MPSM are the superposition of results calculated by SPSM. Computational efficiency of MPSM is lower than that of SPSM due to the large model scale. SPSM is suggested to study the static performance of the coupled system and to perform parametric analysis in dynamic investigation, while MPSM is suggested to investigate the system dynamics in frequency-domain.